Model SECI dalam Praktik Konversi Pengetahuan UMKM di Kota Bogor: Sebuah Kajian Kualitatif - Muhammad Faishal Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze knowledge conversion practices in Micro, Small, and Medium Enterprises (MSMEs) based on the SECI Model (Socialization, Externalization, Combination, Internalization) framework and to identify supporting and inhibiting factors influencing the process within business management dynamics. The research employed a qualitative approach with a case study design involving MSMEs in Bogor City. Data were collected through observation and in-depth interviews with business owners and employees and analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that knowledge conversion practices have not been fully implemented according to the complete SECI cycle and remain dominated by the socialization and externalization stages, which occur informally. Meanwhile, the combination and internalization stages have not been optimally implemented due to limitations in managerial literacy, technological utilization, and organizational capacity. Supporting factors include a communicative work culture, close interpersonal relationships among business actors, and access to training and external networks. This study highlights the importance of strengthening structured knowledge management systems to enhance MSMEs’ competitiveness and sustainability.